The Effect of Organizational Culture on Employee Performance Mediated by Work Motivation at PT. Permodalan Nasional Madani Cianjur Branch - Tarjono; Masoud Ghorbanhosseini (Involvement International Journal of Business, 2024)
This study aims to examine the effect of organizational culture on employee performance through employee work motivation at PT Permodalan Nasional Madani Cianjur Branch. This research uses a quantitative approach with Structural Equation Modeling (SEM) using the SmartPLS program. The population used is all employees of PT Permodalan Nasional Madani Cianjur Branch. The sample consisted of 102 respondents. The data collection technique was carried out using a questionnaire distributed online. The results showed that work motivation can significantly mediate the effect of organizational culture on employee performance at PT Permodalan Nasional Madani Cianjur Branch. The result of Direct Effect Analysis is BO -> MK : Original Sample (Path) = 0,693; t-Statistics = 10,788; P-Values = 0,000; Decision = Positive. BO -> KK : Original Sample (Path) = 0,068; t-Statistics = 1,949 P-Values = 0,052; Decision = Positive. MK -> KK : Original Sample (Path) = 0,760; t-Statistics = 13,294; P-Values = 0,000; Decision = Positive.